On the baseline evolution of automobile fuel economy in Europe - Zachariadis, Theodoros (My University, 2006)
‘Business as usual’ scenarios in long-term energy forecasts are crucial for scenario-based policy analyses. This article focuses on fuel economy of passenger cars and light trucks, a long-disputed issue with serious implications for worldwide energy use and CO2 emissions. The current status in Europe is explained and future developments are analysed with the aid of historical data of the last three decades from the United States and Europe. As a result of this analysis, fuel economy values are proposed for use as assumptions in baseline energy/transport scenarios in the 15 ‘old’ European Union Member States. Proposed values are given for new gasoline and diesel cars and for the years 2010, 2020 and 2030. The increasing discrepancy between vehicle fuel consumption measured under test conditions and that in the real world is also considered. One main conclusion is that the European Commission's voluntary agreement with the automobile industry should not be assumed to fully achieve its target under baseline conditions, nor should it be regarded as a major stimulus for autonomous vehicle efficiency improvements after 2010. A second conclusion is that three very recent studies enjoying authority across the EU tend to be overly optimistic as regards the technical progress for conventional and alternative vehicle propulsion technologies under ‘business as usual’ conditions.
Keywords: Road transport; Efficiency; CO2 emissions